Troubles in the heart of the EU – Political crisis in Belgium - Van den Bosch, Jeroen (Wydział Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2011)
This article looks for the causes of the Belgian crisis in its history, political reforms and identity changes. It further analyzes what might be the consequences of these changes for Belgium and Europe.
Troubles in the heart of the EU - Political crisis in Belgium